DIGITAL COMMUNICATION STRATEGY OF THE @TEATERKELILINGIND INSTAGRAM ACCOUNT IN PROMOTING IMMORTAL THE MUSICAL: SI PITUNG - Cahya Wulandari Purnomo; RR. Roosita Cindrakasih (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
This study aims to analyze the digital communication strategy implemented by the @teaterkelilingind Instagram account in promoting the production of Immortal The Musical: Si Pitung. The research focuses on how Teater Keliling packages traditional cultural content to make it relevant and appealing to the younger generation through social media. A descriptive qualitative approach underpinned by the Computer Mediated Communication (CMC) theory was utilized in this study. Data collection was conducted through content observation, documentation, and in depth interviews with the production manager, head of social media, and a key informant from the audience. The results indicate that @teaterkelilingind successfully builds audience engagement by implementing a "stick to the value" strategy, modifying narratives with modern romance, and optimizing Instagram features such as Reels, Feeds, and Stories using the inclusive greeting "warga". From a CMC perspective, this digital interaction overcomes the limitations of physical cues through interactive, hyperpersonal communication. Despite facing obstacles like algorithmic opacity, consistent content planning remains the primary supporting factor for the promotional success of this production.